Impact of sternotomy and pericardiotomy on cardiopulmonary haemodynamics in a large animal model. Issue 5 (9th March 2023) - Kirk, Mathilde Emilie; Merit, Victor Tang; Moeslund, Niels; Dragsbaek, Simone Juel; Hansen, Jacob Valentin; Andersen, Asger; Lyhne, Mads Dam
Abstract : New Findings: What is the central question of this study? Invasive cardiovascular instrumentation can occur through closed‐ or open‐chest approaches. To what extent will sternotomy and pericardiotomy affect cardiopulmonary variables? What is the main finding and its importance? Opening of the thorax decreased mean systemic and pulmonary pressures. Left ventricular function improved, but no changes were observed in right ventricular systolic measures. No consensus or recommendation exists regarding instrumentation. Methodological differences risk compromising rigour and reproducibility in preclinical research. Abstract: Animal models of cardiovascular disease are often evaluated by invasive instrumentation for phenotyping. As no consensus exists, both open‐ and closed‐chest approaches are used, which might compromise rigour and reproducibility in preclinical research. We aimed to quantify the cardiopulmonary changes induced by sternotomy and pericardiotomy in a large animal model. Seven pigs were anaesthetized, mechanically ventilated and evaluated by right heart catheterization and bi‐ventricular pressure–volume loop recordings at baseline and after sternotomy and pericardiotomy. Data were compared by ANOVA or the Friedmann test where appropriate, with post‐hoc analyses to control for multiple comparisons. Sternotomy and pericardiotomy caused reductions in mean systemic (−12 ± 11 mmHg, P  = 0.027) and pulmonary pressures (−4 ± 3 mmHg, P  = 0.006) and airway pressures. Cardiac output decreased non‐significantly (−1329 ± 1762 ml/min, P  = 0.052). Left ventricular afterload decreased, with an increase in ejection fraction (+9 ± 7%, P  = 0.027) and coupling. No changes were observed in right ventricular systolic function or arterial blood gases. In conclusion, open‐ versus closed‐chest approaches to invasive cardiovascular phenotyping cause a systematic difference in key haemodynamic variables. Researchers should adopt the most appropriate approach to ensure rigour and reproducibility in preclinical cardiovascular research.